Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Rohmatulloh Wahyu Pradana; Dwi Ermayanti Susilo (Journal on Education, 2023)
An essential concept element for investors is enterprise value, which is a gauge of how the market values a company overall. Examining the company's corporate social responsibility is the goal of this study. Furthermore, we look into how profitability might act as a moderator in the relationship between company value and corporate social responsibility. The research sample consisted of transportation and logistics companies that were listed on the Indonesia Stock Exchange (BEI) during the 2021–2022 period. Purposive sampling was used to get samples. Secondary data was gathered from the annual reports and financial reports for 2021–2022 for each sample, or a total of 28 enterprises, using a documentation research gathering approach. In this study, standard assumption testing, hypothesis testing, and moderated regression analysis are among the quantitative methods used. The findings of studies conducted with SPSS 26 demonstrate that corporate social responsibility (CSR) affects business value and profitability, with return on equity (ROE) serving as a moderating variable. However, the relationship between CSR and business value cannot be strengthened.